Does Helicobacter pylori infection have a role in coronary artery disease? - Ahmet AYDIN,; Rukiye VARDAR,; Harun EVRENGÜL,; Mehmet UNGAN,; Mustafa YILMAZ,; Serdar PAYZIN, (Turkish Journal of Gastroenterology, 2019)
-